2022
DOI: 10.3390/ijms23105564
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High-Energy Diet during Pregnancy and Lactation Impairs Neurogenesis and Alters the Behavior of Adult Offspring in a Phenotype-Dependent Manner

Abstract: Obesity is one of the biggest and most costly health challenges the modern world encounters. Substantial evidence suggests that the risk of metabolic syndrome or obesity formation may be affected at a very early stage of development, in particular through fetal and/or neonatal overfeeding. Outcomes from epidemiological studies indicate that maternal nutrition during pregnancy and lactation has a profound impact on adult neurogenesis in the offspring. In the present study, an intergenerational dietary model emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 153 publications
(194 reference statements)
1
3
0
Order By: Relevance
“…In this sense, it has also been shown that the increase in AHN by physical exercise [81] or in transgenic mouse models [82] reduces age-related cognitive decline. In addition, studies indicate that a maternal HF during the perinatal period decreases cell proliferation and differentiation during AHN, altering memory [83,84]. However, other studies agree with our results, showing an increase in the number of stem cells and newly formed neurons in offspring whose mothers were fed a HF.…”
Section: Discussionsupporting
confidence: 87%
“…In this sense, it has also been shown that the increase in AHN by physical exercise [81] or in transgenic mouse models [82] reduces age-related cognitive decline. In addition, studies indicate that a maternal HF during the perinatal period decreases cell proliferation and differentiation during AHN, altering memory [83,84]. However, other studies agree with our results, showing an increase in the number of stem cells and newly formed neurons in offspring whose mothers were fed a HF.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, animal studies have shown that the offspring born to obese dams display reduced working, spatial, and associative memory 14–17 . Several mechanisms have been proposed to underpin the cognitive deficits in the offspring of obese mothers including impaired expression of BDNF and reduced neurogenesis and dendritic arborisation in the hippocampus 18–21 …”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Several mechanisms have been proposed to underpin the cognitive deficits in the offspring of obese mothers including impaired expression of BDNF and reduced neurogenesis and dendritic arborisation in the hippocampus. [18][19][20][21] There is also a large body of evidence demonstrating that paternal obesity predisposes the offspring to metabolic diseases. [22][23][24][25] However, whether brain function can be affected by the obese state of the father, has been barely examined.…”
Section: Introductionmentioning
confidence: 99%
“…In animal studies, maternal consumption of an HFD during pregnancy and lactation has been shown to impair cognitive function in offspring. These offspring exhibit deficits in learning and memory tasks, as well as increased anxiety-like behaviour [ 10 ]. Various mechanisms have been identified to cause cognitive decline in the offspring of maternal subjects that consume an HFD during pregnancy and lactation.…”
Section: Introductionmentioning
confidence: 99%